IDENTIFIKASI FAKTOR PENYEBAB ANAK KELUARGA SEJAHTERA TIDAK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - Fadli M, Achsin; Zakso, Amrazi; Riva'i, Wanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe title of this research is ?The Identification of Causes Factors of Children From The Prosperous Family Who Not Continuing Their Education to The College (Case Study In Pasar Barito Sanggau)?. Common problem in this research is ?Why children from prosperous families there are not continuing their education to the college" (case study in Pasar Barito Sanggau)? The sub-problems are: How is the internal factor that causes the child of traders in Pasar Barito not to continue their education to the college and how is the external factors that cause the child of traders in Pasar Barito not continue their education to the college? The Purpose of this research is to determine the internal and external factors that cause the child of traders in Pasar Barito who not continue their education to college. The techniques of data collection used are interview and documentation studies. The tools of data collection used are interview guides, note books and archives. The analysis in this research is presented by descriptively qualitative by using an 8 informants consisting of 4 children of traders in Pasar Barito who not continue their education to the college, and 4 parents who an traders in Pasar Barito from each that childs. The results of this research that indicate the causes factors of the children from traders in Pasar Barito who not continue their education to the college is the lack of interest from that child of traders to continue their education to the college Keyword :  Causes Factors of Children not to go to The College, Education